Welcome Notes from the Editor-In-Chief - Oniwide, Oyetola (NIU Journal of Social Sciences, 2017)
My Dear Colleagues and Friends:  I am very delighted to bring you this edition of KIU Journal of Social Sciences. Many African countries are facing tremendous economic pressures as globalization continues to be an important factor to contend with in the modern world. The integration of the economic, environmental and socio-cultural systems of the countries of the world is a reality that must be taken seriously.  African countries are scrambling to partner with each other and with other countries around the world in order to achieve significant economic development.  In this issue, the authors of the articles focus on a number of concerns germane to economic development. Some of these include health psychology, social psychology, entrepreneurship studies, governance, development, creative writing, legal studies and educational administration. Human behaviour plays a significant role in most of the leading causes of death. Psychological science has the potential to enhance health outcomes through a better understanding of health promoting and health damaging behaviours. This is why some of the papers dwell on health and social psychology.  It must also be mentioned that in the search for an economic development agenda/program that empowers people, entrepreneurial education is very important in order to achieve a sustainable development. Against this backdrop, some of the papers in this issue amplify that central tenet. Economic transformation is enhanced by investment in technology and industrialization. Many African countries are investing in infrastructures that connect the rural and urban areas and they are diversifying their economic bases. The countries that depend on one resource such as raw material or commodity for their foreign exchange are experiencing a great deal of set-back in their development attempts. Oil rich nations around the world are experiencing economic problems and African countries can learn something from the case of Venezuela in South America. Countries such as Nigeria, Gabon and the Congo should embank on macro-economic reforms for financial sustainability. Solid planning which embraces the findings of comparative and entrepreneurial analysis must become part and parcel of sustainable development across Africa. Sustainable development is impossible without investment in capacity building of citizens. Having a workforce grounded in the understanding of critical thinking and with skills and competencies necessary in the management of companies and businesses is very significant in sustainable development. A few papers in this issue highlight ideas which focus on Africa's "Achilles Heel" and that is the question of leadership. African Countries are inundated with a lot of corrupt leaders and if sustainable development is to be achieved, committed leadership is an imperative. On behalf of the editorial board of the journal, I would like to thank our readership and most all the authors who have worked so hard with us to get the articles to the academic and scholarly communities across the globe. We look forward to your continued support. Sincerely, Oyetola O. Oniwide , Ph.D. Professor of Public Administration, College of Humanities and Social Sciences, Kampala International University, P.O. Box 20000, Kampala, Uganda. editor.socialsciences@kiu.ac.ug March, 2017.